Effect of curing condition on shelf life of fresh potatoes storage in Easter Hararghe zone of Oromia region - Tashome Urge Jiru; Ibsa Aliyi Usmane (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2021)
The quality of potato and its storage life is reduced by the loss of moisture loss, decay and physiological breakdown. These deteriorations are directly related to storage temperature, relative humidity, air circulation and gas composition Curing process which is hardening the skin of potatoes and Bruise prevention is an important part of keeping quality of potatoes with minimum weight loss and storage diseases. The process was facilitated by dark, dry and warm location for six (6), and eight (8) days, at temperature ranges of 17ºC -20ºC and relative's humidity of 74-85 % to healing wound. In addition, curing tubers, the storage has been constructed by integrating the application storage techniques, design factors and management fundamentals into storage systems to minimize the storage losses. As a result of storage good management of the storage temperature observed as 12-16˚C inside and 25-30˚C outside, relative humidity of 77-85 % inside and 40-50 % outside. The observations of weight changes were recorded till end of storage over a 10-14 week throughout storing period with the total physiological loss of 18-24% with loss of (Gudanne < Shantama < Tulema) resulted under six day curing. Total losses include sprouting, greening moisture loss and rotting. Among these (sprouted (%) of lowest mean values loss was resulted as 2.0, 2.01 and 2.5, moisture losses (%) 0.58, 0.56 and 0.63, for variety of gudane, shantama and tulama respectively out of 18 kg before storage, in addition six day curing had significance effect among treatment, on moisture losses, and sprouted, but non significance for rotten and color change at (P< 0.05). As well as the laboratory result of chemical composition of stored tubers were match with that of scientific findings. Since curing and storing of the potato tubers results shows minimal tuber weight loss and chemical composition quality via 10th to 14 week in storage, we recommend farmers to cure before storing the potato tubers under good storage management to slow down deterioration.